Mitochondrial-targeted antioxidant supplementation for improving age-related vascular dysfunction in humans: A study protocol - Murray, Kevin O.; Berryman-Maciel, Morgan; Darvish, Sanna; Coppock, McKinley E.; You, Zhiying; Chonchol, Michel; Seals, Douglas R.; Rossman, Matthew J. (Frontiers in Physiology, 2022)
Background: Cardiovascular disease (CVD) is the leading cause of death worldwide and aging is the primary risk factor for the development of CVD. The increased risk of CVD with aging is largely mediated by the development of vascular dysfunction. Excessive production of mitochondrial reactive oxygen species (mtROS) is a key mechanism of age-related vascular dysfunction. Therefore, establishing the efficacy of therapies to reduce mtROS to improve vascular function with aging is of high biomedical importance. Previously, in a small, randomized, crossover-design pilot clinical trial, our laboratory obtained initial evidence that chronic oral supplementation with the mitochondrial-targeted antioxidant MitoQ improves vascular function in healthy older adults. Here, we describe the protocol for an ongoing R01-funded phase IIa clinical trial to establish the efficacy of MitoQ as a therapy to improve vascular function in older adults (ClinicalTrials.gov Identifier: NCT04851288). Outcomes: The primary outcome of the study is nitric oxide (NO)-mediated EDD as assessed by brachial artery flow-mediated dilation (FMDBA). Secondary outcomes include mtROS-mediated suppression of EDD, aortic stiffness as measured by carotid-femoral pulse wave velocity, carotid compliance and β-stiffness index, and intima media thickness. Other outcomes include the assessment of endothelial mitochondrial health and oxidative stress in endothelial cells obtained by endovascular biopsy; the effect of altered circulating factors following MitoQ treatment on endothelial cell NO bioavailability and whole cell and mitochondrial reactive oxygen species production ex vivo; and circulating markers of oxidative stress, antioxidant status, and inflammation. Methods: We are conducting a randomized, placebo-controlled, double-blind, parallel group, phase IIa clinical trial in 90 (45/group) healthy older men and women 60 years of age or older. Participants complete baseline testing and are then randomized to either 3 months of oral MitoQ (20mg; once daily) or placebo supplementation. Outcome measures are assessed at the midpoint of treatment, i.e., 6 weeks, and again at the conclusion of treatment. Discussion: This study is designed to establish the efficacy of chronic supplementation with the mitochondrial-targeted antioxidant MitoQ for improving vascular endothelial function and reducing large elastic artery stiffness in older adults, and to investigate the mechanisms by which MitoQ supplementation improves endothelial function.